GESTALT SIMPLIFICATION: BIBLE STORY ANIMATION 'THE PRODIGAL SON' - Darmawan, Andreas James; Arimbawa, I Made Gede; Muka, I Ketut; Suardina, I Nyoman (ISI Press Institut Seni Indonesia Surakarta, 2025)
Bible story animation 'The Prodigal Son' only presents the storyline without touching the theological meaning. Church youth experience boredom in understanding parable story of 'Prodigal Son'. The problem urgency is the lack of teaching media that convey repentance, forgiveness, and gratitude meaning in an interesting and contextual way. This study used descriptive qualitative method through literature, discussions, and FGD. The creation process involved application of Edgar Rubin's visual simplification theory and Max Wertheimer's, Wolfgang Köhler, Kurt Koffka Gestalt theory; combined with philosophy, hermeneutics, semiotics; to create new interesting and meaningful animation. The animation successfully visualizes the theological essence of repentance, forgiveness, and gratitude through simplified forms and meaningful gestalt compositions, offering a fresh visual narrative that resonates and supports deeper spiritual reflection for adolescent.